Google classroom for librarians: features and opportunities. Issue 9 (2nd November 2015) - Izenstark, Amanda; Leahy, Katie L.
Abstract : Purpose: – The purpose of this paper is to share possible opportunities for librarians, faculty and students with access to Google Classroom, and it includes a discussion of its application and functionality in information literacy sessions. Design/methodology/approach: – This paper describes the functionality of Google Classroom with a review of its capabilities for providing information literacy instruction based on hands-on use in several classes and observation. Findings: – Google Classroom streamlined delivery of materials with students in one-time and multi-meeting classes. Students appreciated its seamless integration with their university email accounts. Originality/value: – Librarians teaching classes often need to share introductory information, exercises and supplemental materials with students. Google Classroom offers a simple platform for this purpose.